Vitamin C consumption does not impair training-induced improvements in exercise performance - Roberts, L. A.; Beattie, K.; Close, G. L.; Morton, J. P. (International Journal of Sports Physiology and Performance, 2011)
Purpose: To test the hypothesis that antioxidants can attenuate high-intensity interval training-induced improvements in exercise performance. Methods: Two groups of recreationally active males performed a high-intensity interval running protocol, four times per week for 4 wk. Group 1 (n = 8) consumed 1 g of vitamin C daily throughout the training period, whereas Group 2 (n = 7) consumed a visually identical placebo. Pre- and posttraining, subjects were assessed for VO2max, 10 km time trial, running economy at 12 km/h and distance run on the YoYo intermittent recovery tests level 1 and 2 (YoYoIRT1/2). Subjects also performed a 60 min run before and after training at a running velocity of 65% of pretraining VO2max so as to assess training-induced changes in substrate oxidation rates. Results: Training improved (P < .0005) VO2max, 10 km time trial, running economy, YoYoIRT1 and YoYoIRT2 in both groups, although there was no difference (P = .31, 0.29, 0.24, 0.76 and 0.59) between groups in the magnitude of training-induced improvements in any of the aforementioned parameters. Similarly, training also decreased (P < .0005) mean carbohydrate and increased mean fat oxidation rates during submaximal exercise in both groups, although no differences (P = .98 and 0.94) existed between training conditions. Conclusions: Daily oral consumption of 1 g of vitamin C during a 4 wk high-intensity interval training period does not impair training-induced improvements in the exercise performance of recreationally active males.